150k views
3 votes
Jason knows that the equation to calculate the period of a simple pendulum is , where T is the period, L is the length of the rod, and g is the acceleration due to gravity. He also knows that the frequency (f) of the pendulum is the reciprocal of its period. How can he express L in terms of g and f?

Jason knows that the equation to calculate the period of a simple pendulum is , where-example-1
User Kortschak
by
5.3k points

2 Answers

3 votes

Answer-


\boxed{\boxed{L=(g)/(4\pi^2 f^2)}}

Solution-

The equation for time period of a simple pendulum is given by,


T=2\pi \sqrt{(L)/(g)}

Where,

T = Time period,

L = Length of the rod,

g = Acceleration due to gravity.

Frequency (f) of the pendulum is the reciprocal of its period, i.e


f=(1)/(T)\ \Rightarrow T=(1)/(f)

Putting the values,


\Rightarrow (1)/(f)=2\pi \sqrt{(L)/(g)}


\Rightarrow ((1)/(f))^2=(2\pi \sqrt{(L)/(g)})^2


\Rightarrow (1)/(f^2)=4\pi^2 (L)/(g)


\Rightarrow L=(g)/(4\pi^2 f^2)

7 votes
1/f = 2π√(L/g)
1/(2πf) = √(L/g) . . . . . divide by 2π
1/(2πf)^2 = L/g . . . . . .square both sides
g/(2πf)^2 = L . . . . . . .multiply by g

L = g/(4π^2f^2) . . . . . . . matches the 1st selection
User Nick Zuber
by
5.3k points